Biological Activities and Emerging Roles of Lignin and Lignin-Based ProductsA Review - Shu, Fan; Jiang, Bo; Yuan, Yufeng; Li, Mohan; Wu, Wenjuan; Jin, Yongcan; Xiao, Huining (Biomacromolecules, 2021)
Bioactive substances, displaying excellent biocompatibility, chemical stability, and processability, could be extensively applied in biomedicine and tissue engineering. In recent years, plant-based bioactive substances such as flavonoids, vitamins, terpenes, and lignin have received considerable attention due to their human health benefits and pharmaceutical/medical applications. Among them is lignin, an amorphous biomacromolecule mainly derived from the combinatorial radical coupling of three phenylpropane units (p-hydroxypenyl, guaiacyl, and syringyl) during lignification. Lignin possesses intrinsic bioactivities (antioxidative, antibacterial, anti-UV activities, etc.) against phytopathogens. Lignin also enhances the plant resistance (adaptability) against environmental stresses. The abundant structural features of lignin offer other significant bioactivities including antitumor and antivirus bioactivities, regulation of plant growth, and enzymatic hydrolysis of cellulose. This Review reports the latest research results on the bioactive potential of lignin and lignin-based substances in biomedicine, agriculture, and biomass conversion. Moreover, the interfacial reactions and bonding mechanisms of lignin with biotissue/cells and other constituents were also discussed, aiming at promoting the conversion or evolution of lignin from industrial wastes to value-added bioactive materials.